When Liability is Not Enough: Regulating Bonus Payments in Markets With Advice - Jun Honda; Roman Inderst; Marco Ottaviani (ZBW - Leibniz Information Centre for Economics, 2022)
We introduce a model of advice in which firms steer advisors through nonlinear incentive schemes. In addition to developing an isomorphism to pricing with mixed bundling, we obtain three main insights. First, firms optimally use nonlinear bonuses to economize on the rent paid to advisors. Second, equilibrium bonus payments induce advisors to make biased recommendations that are artificially contingent on each other, resulting in an inefficient allocation. Third, if advisor liability is stepped up, firms respond by increasing the size of the bonus, leaving advisor bias unchanged. These results support direct regulatory interference on the way advisors are compensated.
Keywords: 330; bonus payments; nonlinear incentive schemes; advisor incentivization